(untitled) (Journal of Universal Excellence, 2026)
Research question: What kind of long-term care services the seniors in nursing homes and their relatives, as well as the future users in Slovenia, prefer. Is the ranking list the same as in the USA, like presented by Black and Dobbs (2015, str. 133-152)? Purpose: This article presents the problems of quality of long-term care and especially nursing as a part thereof. It shows the results of research of what matters most to current residents of Slovenian nursing homes, their relatives and future users of long-term care services in Slovenia. Method: After our study of the relevant European and OECD literature we found that the development of quality standards and norms in long-term care for seniors can be developed in different ways. To identify the preferred indicators of quality of long-term care, we had three groups of interviews with nursing home residents and their relatives from three Slovenian municipalities and analysed them. Results: We found that there is a substantial gap between the needs and the availabilities of long-term care arrangements in Slovenia. The results show which indicators of quality of LTC matters most to residents and their relatives and what prefer each group. The ranking list is different for each group and is not the same as the ranking list of Black and Dobbs. Local administration and society: These findings refer to the positive local administration initiative to develop community services and nursing homes for seniors with decreasing functional capacities by municipalities themselves, or to develop conditions for private investments in local areas that would attract investments in affordable community services and nursing homes for seniors. Novelty: This study is the first of its kind in Slovenia while its results provide better insight into what matters most to Slovenian seniors and their relatives regarding the quality of their Long Term Care. It also initiated a further study of the first author which lead to her Ph.D. thesis. Further extension: The study could give different results in the case of metropolitan areas, e.g. for the case of Ljubljana. Therefore the study should be extended to investigate the urban population.